Individualism, Opportunism, and the preference for direct foreign investment across cultures - Shane, Scott (School of Management Working Papers, 1990)
This article argues that differences in the preference for direct foreign investment across countries is explained by differences in the degree of individualism of the members of these societies. Individualism increases perceptions of opportunism and the transaction costs of exporting. These perceptions are projected by investors on their counterparts because of false consensus, leadinr,i squared individualism ratings to determine the preference for foreign direct investment. Squared individualism scores are found to explain 46.1 % of the variance in the tendency to engage in foreign direct investment across 25 countries. Adding economic factors - technology and wealth - improves the equation so that it explains 62.5% of the variance.